2023
DOI: 10.7717/peerj.14556
|View full text |Cite
|
Sign up to set email alerts
|

Differences in histomorphology and expression of key lipid regulated genes of four adipose tissues from Tibetan pigs

Abstract: Tibetan pigs, an indigenous pig breed in China, have high overall fat deposition and flavorful and tasty meat. They are thus good models for studying adipogenesis. Few studies have been conducted focusing on expression of lipid regulated genes in different adipose tissues of Tibetan pigs. Therefore, we compared the difference of histomorphology and expression level of lipid regulated genes through qPCR and western blot in subcutaneous fat, perirenal fat, omental adipose tissue, and inguinal fat of Tibetan pigs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Fifty-two DEGs were filtered out and 18 down- and 34 up-regulated genes were presented in the IMF group. Functional analysis of these DEGs showed that these targets were primarily associated with lipid metabolism, energy metabolites and amino acid biosynthesis and degradation, such as lipid metabolic process [ 71 ], valine, leucine and isoleucine degradation [ 72 ], peroxisome [ 73 ], apelin signaling pathway [ 74 ]. Subsequently, ACTA2 and HMGCL were screened as potential biomarkers specific to IMF deposition through bioinformatics and three machine learning approaches, with ACTA2 in particular identified as the most potentially sensitive biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty-two DEGs were filtered out and 18 down- and 34 up-regulated genes were presented in the IMF group. Functional analysis of these DEGs showed that these targets were primarily associated with lipid metabolism, energy metabolites and amino acid biosynthesis and degradation, such as lipid metabolic process [ 71 ], valine, leucine and isoleucine degradation [ 72 ], peroxisome [ 73 ], apelin signaling pathway [ 74 ]. Subsequently, ACTA2 and HMGCL were screened as potential biomarkers specific to IMF deposition through bioinformatics and three machine learning approaches, with ACTA2 in particular identified as the most potentially sensitive biomarker.…”
Section: Discussionmentioning
confidence: 99%